Modeling a Generalized Resource Constrained Multi Project Scheduling Problem Integrated with a Forward-Backward Supply Chain Planning. Issue 12 (2016) - Gholizadeh-Tayyar, S.; Dupont, L.; Lamothe, J.; Falcon, M.
Abstract: Generalized Resource Constrained Multi Project Scheduling Problem, GRCMPSP, is issue of determining a scheduling plan for executing projects' activities under satisfaction of precedence relationship between activities and availability of resources. This paper focuses on the resources' availability. To deal with feeding nonrenewable recourses over periods they are demanded and to define a production-transportation plan for them, our proposed mixed integer programming model integrates GRCMPSP with Supply Chain Planning model. Also, to establish a plan for assigning required amounts of renewable resources, it supposes possibility of renting supplementary quantities. This assumption leads the model to define an optimum assignment under considering rent cost of additional resources and penalty cost may originate from lateness of the activities. The results are shown from applying the model on a project called CRIB A, which is defined to reduce energy consumption level of buildings in France.